Effect of combined home-based, overground robotic-assisted gait training and usual physiotherapy on clinical functional outcomes in people with chronic stroke: A randomized controlled trial. (June 2021) - Wright, Amy; Stone, Keeron; Martinelli, Louis; Fryer, Simon; Smith, Grace; Lambrick, Danielle; Stoner, Lee; Jobson, Simon; Faulkner, James
Objectives: To assess the effect of a home-based over-ground robotic-assisted gait training program using the AlterG Bionic Leg orthosis on clinical functional outcomes in people with chronic stroke. Design: Randomized controlled trial. Setting: Home. Participants: Thirty-four ambulatory chronic stroke patients who recieve usual physiotherapy. Intervention: Usual physiotherapy plus either (1)10-week over-ground robotic-assisted gait training program ( n = 16), using the device for ⩾30 minutes per day, or (2) control group ( n = 18), 30 minutes of physical activity per day. Measurements: The primary outcome was the Six-Minute Walk Test. Secondary outcomes included: Timed-Up-and-Go, Functional Ambulation Categories, Dynamic Gait Index and Berg Balance Scale. Physical activity and sedentary time were assessed using accelerometry. All measurements were completed at baseline, 10 and 22 weeks after baseline. Results: Significant increases in walking distance were observed for the Six-Minute Walk Test between baseline and 10 weeks for over-ground robotic-assisted gait training (135 ± 81 m vs 158 ± 93 m, respectively; P ⩽ 0.001) but not for control (122 ± 92 m vs 119 ± 84 m, respectively). Findings were similar for Functional Ambulation Categories, Dynamic Gait Index and Berg Balance Scale (all P ⩽ 0.01). For over-ground robotic-assisted gait training, there were increases in time spent stepping, number of steps taken, number of sit-to-stand transitions, and reductions in time spent sitting/supine between baseline and 10 weeks (all P < 0.05). The differences observed in all of the aforementioned outcome measures were maintained at 22 weeks, 12 weeks after completing the intervention (all P > 0.05). Conclusion: Over-ground robotic-assisted gait training combined with physiotherapy in chronic stroke patients led to significant improvements in clinical functional outcomes and physical activity compared to the control group. Improvements were maintained at 22 weeks.